Biosystem Assembly: Origami Biosystems: 3D Assembly Methods for Biomedical Applications (Adv. Biosys. 12/2018). Issue 12 (7th December 2018) - Bolaños Quiñones, Vladimir A.; Zhu, Hong; Solovev, Alexander A.; Mei, Yongfeng; Gracias, David H.
Abstract : 3D assembly methods based on bending, curving and folding are important for the integration of advanced biosystems. In article number1800230, David H. Gracias and co‐workers classify these origami and biologically inspired methods and discuss important advances of relevance to biomolecular systems, sensing, microfluidics, robotics, drug delivery, and cell and tissue engineering.